The Impact of Cognitive and Metacognitive Strategies on Iranian EFL Bilingual versus Monolingual Learners Reading Comprehension ability (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study attempts to measure the effect of the implementation of cognitive and metacognitive reading strategies on reading ability of second year high school students who were bilinguals and monolinguals. In order to address these issues, a quantitative study was conducted on 193 EFL bilingual and monolingual students who were randomly selected from some high schools of Markazi province (Arak and Farahan ) . To meet the mentioned aims, subjects were given English proficiency test, reading comprehension test, cognitive and metacognitive strategies questionnaire By utilizing t-test and ANOVA revealed that there would be statistically significant differences between the above-mentioned subjects as follows:1-There wasn't meaningful difference between female bilingual and female monolingual learners in using cognitive and metacognitive strategies .2- There was meaningful difference between male bilingual and male monolingual learners in using cognitive and metacognitive strategies .3- Gender didn't have significant effect on using cognitive and metacognitive strategies in EFL learners reading comprehension ability.